2019
DOI: 10.47102/annals-acadmedsg.v48n6p171
|View full text |Cite
|
Sign up to set email alerts
|

Multidomain Geriatric Screen and Physical Fitness Assessment Identify Prefrailty/Frailty and Potentially Modifiable Risk Factors in Community-Dwelling Older Adults

Abstract: Introduction: Frailty begins in middle life and manifests as a decline in functional fitness. We described a model for community frailty screening and factors associated with prefrailty and frailty and fitness measures to distinguish prefrail/frail from robust older adults. We also compared the Fatigue, Resistance, Ambulation, Illnesses and Loss of weight (FRAIL) scale against Fried frailty phenotype and Frailty Index (FI). Materials and Methods: Community-dwelling adults >55 years old were designated robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…The total regression model for the FP demonstrated a significant relationship between frailty and dexterity performance whereas the FI was associated with lower extremity performance. Previous evidence demonstrated that upper limb dexterity performance might differentiate robust from pre-frail/frail individuals [58]. In our descriptive analyses, we also found a significantly lower dexterity performance in frail vs. pre-frail subjects as determined by the FP suggesting that also within the group of prefrail and frail subjects, upper extremity function is related to the degree of frailty.…”
Section: Sensory and Motor Correlates Of Frailty Depending On Frailty...supporting
confidence: 71%
“…The total regression model for the FP demonstrated a significant relationship between frailty and dexterity performance whereas the FI was associated with lower extremity performance. Previous evidence demonstrated that upper limb dexterity performance might differentiate robust from pre-frail/frail individuals [58]. In our descriptive analyses, we also found a significantly lower dexterity performance in frail vs. pre-frail subjects as determined by the FP suggesting that also within the group of prefrail and frail subjects, upper extremity function is related to the degree of frailty.…”
Section: Sensory and Motor Correlates Of Frailty Depending On Frailty...supporting
confidence: 71%
“…As illustrated in Fig. 2 A and B, frailty [ 18 , 19 ], cognitive impairment [ 40 ], functional decline [ 41 ] and poor oral intake during admission would have been descendants of depressive symptoms and malnutrition, and thereby considered mediators in the causal paths between depressive symptoms or malnutrition and 30-day readmission. In conventional analyses that adjusted for these mediators, we failed to observe associations between depressive symptoms and malnutrition on readmission, plausibly due to bias introduced by overadjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and malnutrition represent modifiable factors to address readmission risk, having been associated across studies with readmission outcomes although their causal pathways were not always explicitly described [ 13 , 15 – 17 ]. Additionally, both are common risk factors for other geriatric syndromes such as frailty and cognitive impairment [ 18 , 19 ], and potentially predispose to intermediary events including functional decline and poor oral intake during the index admission, all of which may further contribute to the patient’s risk for readmission. Thus, with hospital readmissions in older adults being typically complex and multifactorial, we propose the use of graphical representations of exposure-outcome relationship to facilitate analysis for a less biased estimate of the total causal effect of depression and malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…This cross-sectional study included community-dwelling ambulant adults over 50 years old who volunteered to participate in the "Individual Physical Proficiency Test for Seniors" (IPPT-S)a community-based programme designed to promote fitness and to prevent or delay sarcopenia and frailty in older adults. 7 Exclusion criteria included residents of sheltered or nursing homes, and the inability to ambulate at least 4 m (with or without an assistive device). The institutional review board approved the study (SingHealth CIRB 2018/2115, Singapore), and all participants provided written informed consent.…”
Section: Participantsmentioning
confidence: 99%